Marketing Politik Elisabeth Nauw Pada Pemilihan Legislatif 2019 di Kota Sorong - Banggu, Masni; Obadiri, Abrian Olfen; Purwanti, Nanik; Kalagison, Miryam Diana (Jurnal Fase Kemajuan Sosial dan Politik: Faksi, 2023)
This research aims to describe and analyze Elisabeth Nauw's victory in the 2019 Sorong City legislative election through political marketing and the social capital used. The research method uses a qualitative approach with data collection techniques carried out through direct field observations, in-depth interviews with informants, and literature reviews through published articles or journals related to the author's research focus. For the technique of determining informants, the author chooses people who are considered capable of answering questions related to the focus of the author's research. The results of this research describe Elisabeth Nauw's victory, namely first, Elisabeth Nauw is a personal characteristic of a leader or candidate who provides an image, symbol or political product in an election. Second, promotion in this case won constituent votes, Elisabeth Nauw was assisted by the winning team, and campaigned via social media. Third, the price is the total cost of campaign activities carried out by the candidate and winning team. Fourth, a place is an area where the majority of the population has the same ethnicity as the candidate so that it is easy to get constituent votes.